Understanding the Rights of Wife in The Law Number 1 of 1974 About Marriage Among the Terrorist Wives in Central Java - Rosdiana Rosdiana; Hotnidah Nasution (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe terrorist or ex-terrorist wives in Solo Central Java have experienced diverse conditions after their husband officially becomes a terrorist prisoner. The Rights of Wife in Law No. 1 of 1974 about Marriage among terrorist wives in Solo have sharpened the analysis on how their level of perception of the wife rights that regulated by Law No. 10 of 1974. This study aims to reveal the reality of cases that take place with terrorist wifes related to the fulfilment of their rights as a wife regulated by law, and to categorize their marital status related to the validity in a positive law (whether the marriage is registered or not in The Office of Religious Affairs/KUA). Besides, this paper also wants to explore the terrorist wife’s understanding who are legally married in KUA regarding their rights which are highly protected by the law. This research uses a qualitative method which aims to find concept and theory, and library research by applying the empirical or sociological legal approach. Data used are Primary Data, namely the terrorist prisoner’s wives in Solo Central Java, and secondary data from the Marriage Law (Law No. 1 of 1974), Compilation of Islamic Law (KHI), books, journals, articles, doctrine of legal experts, and the result of other papers and research related to the problem that become the subject in this research discussion. After analyzing and interpreting the existing data, it can be concluded that the terrorist prisoner wives in Solo Central Java have a fairly good understanding of their rights as wives regulated in Law No. 1 of 1974. If there are rights that unfulfilled by the husband, they will accept as sincerity attitude towards the husband status who becomes a prisoner. Keywords: Understanding, wife's rights, Terrorist Prisoner’s Wives AbstrakPara istri teroris atau mantan teroris di Solo telah mengalami kondisi yang beragam setelah suami mereka secara resmi menjadi tahanan teroris yang telah tinggal di penjara. Hak-Hak Istri dalam UU No. 1 tahun 1974 tentang Perkawinan di antara istri-istri teroris di Solo telah mempertajam analisis tentang bagaimana tingkat persepsi mereka tentang hak-hak istri yang diatur oleh UU No. 10 tahun 1974. Penelitian ini bertujuan untuk mengungkap kenyataan dari kasus-kasus yang terjadi dengan istri-istri teroris terkait dengan pemenuhan hak-hak mereka sebagai seorang istri yang diatur oleh hukum, dan untuk mengkategorikan status perkawinan mereka terkait dengan validitas dalam hukum positif (apakah pernikahan terdaftar atau tidak di Kantor Urusan Agama (KUA)). Selain itu, makalah ini juga ingin mengeksplorasi pemahaman istri teroris yang menikah secara resmi di KUA tentang hak-hak mereka yang sangat dilindungi oleh hukum. Penelitian ini menggunakan metode kualitatif yang bertujuan untuk menemukan konsep dan teori, dan penelitian kepustakaan dengan menerapkan pendekatan hukum empiris atau sosiologis. Sumber data yang digunakan adalah Data Primer, yaitu istri-istri tahanan teroris di Solo, dan data sekunder dari UU Perkawinan (UU No. 1 tahun 1974), Kompilasi Hukum Islam (KHI), buku, jurnal, artikel, pandangan ahli hukum, dan hasil tulisan dan tulisan lain yang berkaitan dengan masalah yang menjadi subjek dalam diskusi penelitian ini. Setelah menganalisis dan menafsirkan data yang ada, dapat disimpulkan bahwa para istri napi teroris di Jawa Tengah memiliki pemahaman yang cukup baik tentang hak-hak mereka sebagaimana para istri diatur dalam UU No. 1 tahun 1974. Jika saja ada hak yang tidak dijamin oleh mereka untuk kewajiban yang tidak terpenuhi oleh suami, maka itu disebabkan oleh sikap ketulusan mereka terhadap status suami yang menjadi tahanan.Kata Kunci: Pemahaman, hak-hak istri, Istri Tahanan Teroris АннотацияЖены террористов или бывших террористов в городе Соло оказались в разных условиях после того, как их мужья официально стали заключенными террористами. Права жены в Законе № 1 1974 года о браке жен террористов в Соло уточнили с помощью анализа их уровня восприятия о правах жены, которые регулируются Законом № 10 1974 года. Цель этого исследования - раскрыть реальные случаи, которые имели место с женами-террористами, связанные с реализацией их прав в качестве жены, регулируемых законом, и для классификации их семейного положения, связанного с действительностью в позитивном праве (независимо от того, зарегистрирован брак или нет в Управлении по Делам Религии (KUA)). Кроме того, данная статья также исследует понимание жен террористов, которые состояли в законном браке в KUA относительно их прав, которые защищены законом на высоком уровне. В этом исследовании используется качественный метод, нацеленный на поиск концепций и теорий, а также литературные исследования с применением эмпирического или социологического правового подхода. Используемые источники данных: первичные данные, а именно жены заключенных террорисов в Соло, и вторичные данные из Закона о браке, Сборник Исламского Права (KHI), книги, журналы, статьи, мнения экспертов по правовым вопросам, и результаты других работ и статей, связанных с проблемами, которые являются предметом этой научной дискуссии. После анализа и интерпретации существующих данных можно сделать вывод о том, что жены заключенных террористов на Центральной Яве достаточно хорошо понимают свои права как жен, регулируемых Законом № 1 от 1974 года. Если только существуют права, которые они подделывают для невыполненных обязательств мужа, то это обусловлено их искренним отношением к статусу мужа, который становится заключенным.Ключевые слова: Понимание, Права жены, Жены заключённых террористов